Checklist of the mites (Arachnida: Acari) of Turkey.: Second supplement - Erman, Orhan; Oezkan, Muhlis; Ayyildiz, Nusret; Dogan, Salih (Magnolia Press, 2007)
As a suplement to the lists of the mites fauna of Turkey compiled by Ozkan et al. ( 1988 and 1994), a faunistic list of mites ( Arachnida: Acari) from Turkey is presented based on published data. The species are arranged alphabetically within orders and for each entrance the origin of reference to the published record is provided. Among the 504 taxa, 134 belong to the Gamasida, 2 to the Ixodida, 291 to the Actinedida, 7 to the Acaridida and 70 to the Oribatida.
Keywords: Turkey; Acari; taxonomy; checklist